OPPORTUNITIES FOR IMPROVING TECHNICAL POTENSIAL IN AGRICULTURE BASED ON FOREIGN EXPERIENCES (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the theoretical foundations for improving the agricultural technical service system and explores advanced international experiences in enhancing technical capacity within the sector. The research provides a scientific justification of how the efficient utilization of machinery, the development of service infrastructure, and the expansion of mechanization levels contribute to higher production efficiency. In particular, the experiences of France, Senegal, Mali, Nigeria, India, Germany, China, and Japan are analyzed as representative international models. The findings indicate that strengthening technical potential is achieved not only through increasing the quantity of machinery, but also through the establishment of centralized and cooperative service systems, cost-sharing mechanisms, more intensive use of equipment, and the implementation of digital management solutions. Based on this analysis, the article formulates scientific and practical recommendations aimed at adapting these international practices to national conditions.